Significance of Artificial Intelligence in Medicines - Sahu, Samir; Rout, Udayabhanu; Mohanty , Mihir Narayan (International Journal of Psychosocial Rehabilitation, 2019)
“Artificial Intelligence” (AI) is a common term implying that a computer is used to design intelligent behaviour with very less percentage of human involvement. Artificial Intelligence is generally considered to have begun with the robots inventions. The term applies to a wide range of biomedical products like medical diagnosis, robots, human biology-up and scientific data including the “omics” of today. AI has two main branches of science, which is the subject of this review: physical and virtual. The virtual field encompasses digital methods, including electronic health records, from deep learning information management to control systems in health management and constructive support for physicians in their treatment decision. The best representation for the physical branch is robots used to assist the attending surgeon or elderly patient. Targeted “Nano-robots”, a unique new drug delivery system, are also embodied in that branch. These applications ’ societal and ethical complexities require further reflection, proof of their medical utility, economic value, and the development of interdisciplinary strategies for their wider use.